Utilization of information and communication technology (ICT) in Nigerian educational system: problems and prospects (2010)
Globally, technology has dominated all spheres of human endeavours viz: agriculture, business, medicine, economic, transportation, warfare, education to mention a few. Meanwhile, it is universally recognised that Information and Communication Technology (ICT) be utilized in education as we are now in the era of globalization where information is received through satellite and internet connectivity. However, in Nigeria, the utilization of ICT in education has been confronted with many bottlenecks which this article has tried to address. These bottlenecks include: financial constraints, rationale, erratic power supply, climatic condition, standardization of hardware and software, the place of computer education in the Nigerian school systems, non-availability of facilities and equipment, inadequate skilled manpower and software packages. Others include less accessibility to the internet connectivity and less impact of professional associations’ and organisations’ obligations. Though, despite these setbacks highlighted above there are many prospects for the utilization of ICT in Nigerian educational system as concisely discussed in this presentation.